PUSAT KENDALI RUANG PUBLIK DI BANJARBARU - Rahman, Ulya Hafiza; Saud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
In the government program the 100 Smart City Indonesia Movement. Banjarbaru City is one of the selected cities from the 100 Smart City Indonesia Movement. Building a Command Center of City is one of the basic steps in the Smart City program, especially applied in public spaces. The problem of the Banjarbaru Command Center is still very lacking in various aspects. The Smart Building concept aims to support the city's Command Center. The application of the Smart People principle in adapting the community is sought to support the path of Banjarbaru towards a Smart City.